A review of the Barsine hypoprepioides (Walker, 1862) species-group, with descriptions of fifteen new species and a new subspecies (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel; Huang, Si-Yao (Zootaxa, 2019)
The Barsine hypoprepioides (Walker, 1862) species-group is reviewed. Forty seven species and one subspecies belong to the species-group. Among them, fifteen species and one subspecies are new for science and described in the present paper: B. amoenissima sp. n. (Myanmar), B. selene sp. n. (Thailand and Laos), B. cao sp. n. (Thailand, Laos and Vietnam), B. speideli sp. n. (SE China, Thailand, Laos, Cambodia and Vietnam), B. mesomene sp. n. (NE India, Myanmar, China, Thailand, Laos and Vietnam), B. pandeia sp. n. (Vietnam), B. karenkensis wushipheri ssp. n. (S Taiwan), B. euryphaessa sp. n. (Vietnam), B. ivanovamariae sp. n. (Vietnam and SE China), B. eos sp. n. (Thailand), B. mene sp. n. (Thailand), B. syntypicoida sp. n. (Malaysia and Indonesia), B. dubatolovi sp. n. (The Philippines), B. visaya sp. n. (The Philippines), B. nemea sp. n. (The Philippines) and B. kishidai sp. n. (The Philippines). Eight new combinations are established: B. parameia (Rothschild, 1913), comb. n. B. takamukui (Matsumura, 1927), comb. n., B. karenkensis (Matsumura, 1930), comb. n., B. rhipiptera (Wileman & West, 1928), comb. n., B. chi (Roepke, 1946), comb. nov., B. salakia (Schaus, 1922), comb. n., B. marginis (Fang, 1991), comb. nov. and B. dentata (Wileman, 1910), comb. nov. The lectotype is designated for Lithosia hypoprepioides Walker, 1862. Adults, male and female genitalia of all species are illustrated.